The Effectiveness of Puzzle as Solar System Learning Media for Children with Disabilities - Wahyuni Fajar Arum; Erwan Eko Prasetiyo; Farah Putri Wenang Lusianingrum (Jurnal Pembelajaran Fisika, 2019)
Everyone has their own rights and obligations, especially in terms of education. This has already been stated in the contents of the 1945 Constitution article 31 paragraph 1 which states that every citizen has the right to receive education with the same treatment especially for the children with disabilities. The purpose of this research is to find out the effectiveness of puzzle game in the learning process about solar system for children with disabilities. This research is included as research and development. The research design is quantitative and qualitative. Data collection techniques used in this research are including observation, documentation, and interviews. The results of this study indicate that the use of puzzles has an effectiveness that affects the learning process of solar system material which is showed by the SPSS test. The SPSS test shows that each item in the questionnaire has a value of more than rtable with value of 0.6694.